Empowering learning: a comprehensive study on the impact and efficacy of digital technology integration in UiTM Perak Branch, Tapah Campus / Nor Hazlina Mohammad ... [et al.] - Mohammad, Nor Hazlina; Zulkipli, Faridah; Ahmad, Norhasliza; Mohamad Razi, Nor Faezah; Sarkam, Nor Aslily (2023)
The goal of this study is to investigate the efficacy of using digital technology in teaching and learning. 100 students from the College of Computing, Informatics, and Mathematics took part in this study. The online questionnaire is delivered via WhatsApp, Telegram, and other social media apps. Students benefit from incorporating digital technology into their education by keeping up with the latest technology, having access to course materials 24 hours a day, creating a comfortable and engaging learning environment, preparing students for the future, and encouraging spontaneous learning. Its distinctiveness arises from the flexibility with which course materials can be accessed, collaborative teaching methods, and the addition of gamification aspects. According to the findings, digital technology can assist students in developing a happy learning environment, build self-esteem and confidence, improve soft skills, increase productivity and focus, and improve communication. In addition, the potential for commercialization includes digitizing course materials, accessing a larger student population, and constantly developing teaching and learning methods.